BANDITRY OR INTERPERSONAL ANTAGONISMS?: SOCIAL uSES OF LOCAL ADMINISTRATION OF CRIMINAL JUSTICE IN CHILE: THE CASE OF LINARES. 1804-1871. - Brangier Peñailillo, Víctor (Revista de Historia Social y de las Mentalidades, 2024)
The article looks at the margins of maneuverability that deployed subjects in a rural community, in Linares, throughout nineteenth century, on the stage of criminal justice. We attempted to assess the social use of justice that set the members of the community, from the manipulation of the concept of banditry, judicially reformulating their interpersonal antagonisms. However, this experience would have been suffered turning points as the local justices permeate pressure to impose a judicial bureaucracy, driven by the state throughout the century. The gradual legal subordination of the lay judicial stages, would resenting the malleability with which the residents lawsuit in criminal justice, for definitions of banditry would be imposed according to criminal law was promulgated.